Implementation of Elderly Exercises to Improve Body Health at the Kasih Ibu Galang clinic - Wulan, Sri; Susanti, Plistiana; Istanti, Jannah Triska Tri; Nazwa, Nazwa (JURNAL PENGMAS KESTRA (JPK), 2023)
Elderly age is the final stage of life, where in this elderly phase many changes are experienced by the elderly both physically and mentally. Changes in physical and mental health are a major concern and require a holistic approach to ensure optimal well-being because the health of the elderly is very important to receive attention. Several factors can influence the health of the elderly, such as an inactive lifestyle and lack of attention to physical health, which can cause various health problems. Therefore, there is a need for targeted and sustainable interventions to improve the health of the elderly, one of which is the implementation of special exercises for the elderly. Based on research results, exercise for the elderly has been proven to improve body health and prevent various diseases that arise in the elderly if done regularly. The aim of this Community Service Activity (PKM) is to improve the body health of the elderly. The method used is to check your blood pressure and pulse before exercising and check again after exercising. From the results of the examination, it was found that the majority had normal blood pressure after exercising and a normal pulse after exercising. It is recommended that the elderly continue to carry out exercise regularly to maintain their health, especially physically. Apart from that, they are also advised to pay attention to or implement a healthy daily lifestyle and maintain their physical condition so that they remain in good health.